2017
DOI: 10.1186/s40413-017-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

A partially hydrolyzed 100% whey formula and the risk of eczema and any allergy: an updated meta-analysis

Abstract: BackgroundRecently, the role of using hydrolyzed formula for the prevention of allergic disease has been questioned. However, not all hydrolyzed formulas are equal. The efficacy of each hydrolyzed formula should be established separately. We updated evidence on the effectiveness of using partially hydrolyzed 100% whey formula (pHF), manufactured by a single manufacturer, for reducing the risk of eczema and allergy in healthy infants at high risk for allergy.MethodsThe Cochrane Library, MEDLINE, and EMBASE data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 31 publications
2
53
0
4
Order By: Relevance
“…Interestingly, the effect size observed with pHF-W supplementation is similar to what was observed in trials performed in populations selected with a first-degree relative with allergic disease [2][3][4][5][6]. On explanation could be that, in the general infant population with the genetic bias being weaker than in infants with a first-degree relative with allergic disease, the effect of a change like pHF-W versus CMF may have a better or similar effect due to being less confounded by genetic factors that would favor the development of allergic symptoms regardless of nutritional or environmental pressures.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…Interestingly, the effect size observed with pHF-W supplementation is similar to what was observed in trials performed in populations selected with a first-degree relative with allergic disease [2][3][4][5][6]. On explanation could be that, in the general infant population with the genetic bias being weaker than in infants with a first-degree relative with allergic disease, the effect of a change like pHF-W versus CMF may have a better or similar effect due to being less confounded by genetic factors that would favor the development of allergic symptoms regardless of nutritional or environmental pressures.…”
supporting
confidence: 51%
“…2). Indeed, the effect size (a 30-40% risk reduction at 1 year of age) is comparable to what has been described in a meta-analysis of infants with a family history of AD [2][3][4]6]. However, due to the variability of study design, the different allergic outcomes, the various infant ages at which allergic outcomes were measured, and the possible study selection bias identified in this review, the relevance of the meta-analysis remains low.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, pooling of data on hydrolyzed formulas in meta-analyses may be problematic due to significant heterogeneity of PHF products. A more recent meta-analysis addressed this issue and only included studies using 100%-whey PHF [97]. That study found a preventive effect for all allergies and eczema, but acknowledged limitations in the certainty of available data.…”
Section: Partially Hydrolyzed Formulamentioning
confidence: 99%